Testing of bearing strengths of square and rectangular concrete filled stainless steel tube stub columns under partial compression - Shi, Huai (Nanyang Technological University, 2020)
The purpose of this paper is to study the structural properties of concrete-filled stainless steel tubes (CFSST) stub columns with various concrete strength under partial compression. A total of five series of CFSST stub column test samples were tested throughout the experiment to evaluate the influence of the cross-sections of the square and rectangular sections of the CFSST stub column, including one full compression test from each series for comparison. Given that there have been no existing national codes for the design of bearing strength of partial loaded CFSST stub column. Hence, this report also assesses the suitability of existing corresponding design rules for CFST stub column are used to the design of CFSST stub column, the specific code is in European EN 1994-1-1[12] and American specification AISC 360-16 [13]. The of CFSST stub column bearing strength is obtained based on experimental data. In comparison, it is found that the prediction of bearing strength of CFSST stub column by European Code is fairly close to the experimental results but with slightly unsafe approach; however, the American specifications for the design of bearing strength of CFST column under full compression may not be adequately reflected the design of CFSST column under partial loading.